A magnetic droplet vaporization approach using perfluorohexane-encapsulated magnetic mesoporous particles for ultrasound imaging and tumor ablation. (July 2017) - Teng, Zhaogang; Wang, Ronghui; Zhou, Yang; Kolios, Michael; Wang, Yanjie; Zhang, Nan; Wang, Zhigang; Zheng, Yuanyi; Lu, Guangming
Abstract: Phase change agents consisting of low boiling point perfluorocarbon (PFC) compounds have attracted increasing attention for ultrasound contrast-enhanced imaging and tumor therapy. However, the refraction, acoustic shadowing, reverberation, or limited penetration depth hamper their practical applications through previously reported acoustic droplet vaporization (ADV) or optical droplet vaporization (ODV) technique. Herein, we demonstrate a magnetic droplet vaporization (MDV) approach by loading perflurohexane (PFH) in magnetic mesoporous particles with a hollow space to carry out ultrasound imaging and tumor ablation. In vitro and in vivo magnetic thermal effects show that magnetic energy can be efficiently transformed into thermal energy by the PFH-encapsulated magnetic mesoporous particles, and then leading to vaporization of the loaded PFH. Owing to the generation of the PFH gas bubbles, the ultrasound signals are greatly improved in both harmonic mode and B mode. Simultaneously, anti-cancer experiments demonstrate that the tumor can be ablated after treating with the MDV method for 4 days, demonstrating highly efficient anti-cancer effects.